Israel and the Church God's Road map - Brimmer, Rebecca J. (Jerusalem Bridges for Peace International, 2006)
This anthology, with chapters written by Bridges for peace leaderts around the world, including international president and CEO Rebecca Brimmer, covers topics such as the feasts, aliyah(immigration to Israel), Israel in prophecy, anti-semitism, jerusalem and Replacement Theology
Keywords: Israel-HIstroy and Background -- Feasts - Israel -- Israel-Prophecy